2019
DOI: 10.1111/1744-7917.12695
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the ryanodine receptor mutation I4743M and its contribution to diamide insecticide resistance in Spodoptera exigua (Lepidoptera: Noctuidae)

Abstract: Insect ryanodine receptors (RyRs) are the targets of diamide insecticides. Two point mutations G4946E and I4790M (numbering according to Plutella xylostella, PxRyR) in the transmembrane domain of the insect RyRs associated with diamide resistance have so far been identified in three lepidopteran pests, P. xylostella, Tuta absoluta and Chilo suppressalis. In this study, we identified one of the known RyR target site resistance mutations (I4790M) in a field-collected population of Spodoptera exigua. The field-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 33 publications
(59 reference statements)
4
60
1
2
Order By: Relevance
“…It took just a few years for borderline control failures involving diamide insecticides to emerge in East Asia, with farmers in Jiangsu, China reporting a 44-fold resistance in 2010 (Lai et al 2011; Biondi et al (2018); data from references in text and CABI invasive pest monitoring et al 2013). By 2018, resistance had increased to 150-fold and spread to Shandong (Zuo et al 2019). Now, S. frugiperda is predicted to be heading towards the same area.…”
Section: Tablementioning
confidence: 99%
See 4 more Smart Citations
“…It took just a few years for borderline control failures involving diamide insecticides to emerge in East Asia, with farmers in Jiangsu, China reporting a 44-fold resistance in 2010 (Lai et al 2011; Biondi et al (2018); data from references in text and CABI invasive pest monitoring et al 2013). By 2018, resistance had increased to 150-fold and spread to Shandong (Zuo et al 2019). Now, S. frugiperda is predicted to be heading towards the same area.…”
Section: Tablementioning
confidence: 99%
“…That being said, almost all investigations of TSR-mediated field resistance have found that metabolic pathways also participate. When TSR is isolated against a non-resistant background, resistance levels fall by a factor of ten or more (Douris et al 2017;Zuo et al 2019), suggesting that metabolic effects, although small in isolation, play an important combinatorial role with the more dramatic TSR component.…”
Section: Metabolic Resistancementioning
confidence: 99%
See 3 more Smart Citations